Environmental comfort, functionality, and resident satisfaction: a post-occupancy evaluation in a multi-family residential building - Sidnei, Juliana Rosa; Hilário, Maria Luiza Vieira Xavier; Jesus, Sayonara Lanna Alves de; Paula, Heber Martins de (Brazilian Journal of Production Engineering, 2026)
Brazilian residential buildings, especially those of low and medium standard, often have unsatisfactory performance, even with the possibility of improvements through simple design strategies. In this scenario, Post-Occupancy Evaluation (POE) becomes a fundamental instrument for understanding the real performance of buildings in use, combining technical criteria with user perception, according to ABNT NBR 15575:2024. This study evaluated a medium-standard multi-family residential building in relation to environmental comfort, functionality, safety, and resident satisfaction. The results showed a high level of thermal satisfaction, especially in the kitchen, with 100% acceptance on the "pleasant" scale; the other environments showed small variations between the scales. Regarding natural lighting, there was a predominantly positive performance in the service areas, bedrooms, and bathrooms; evaluations classified as "well lit" or "well lit" obtained 100% of the responses. The evaluation also showed an adequate relationship between spaces and daily activities, with emphasis on the living room as a multi-functional environment.
Keywords: Post-Occupancy Evaluation (POE); Residential performance; Environmental comfort; User satisfaction